REGULASI DIRI PADA IBU TUNGGAL YANG MEMILIKI ANAK REMAJA - Zawil Arham; Bahrun Bahrun; Abu Bakar (Program Studi Bimbingan dan Konseling, FKIP Universitas Syiah Kuala, 2017)
Arham, Zawil 2016. Self Regulation In Single Mothers Who Have Children. Thesis, Department of Guidance and Counseling, the Faculty of Education, University of Syiah Kuala. Supervisor: (1) Dr.Bahrun, M. Pd, (2) Drs. Abu Bakr, M.Si Keywords: Self-Regulation, Single Mother, Teens This study entitled